Design Of Vivaldi Antenna For Non-Destructive Measurement Applications - Mohd Zulfikri, Elvis Syefrizal (2022)
This paper presents an ultra-wideband Vivaldi antenna for non-destructive measurement in 5G applications. The free-space method enables the non-destructive dielectric characterization of materials over a wide frequency range of different material characterization techniques. The use of the Vivaldi antenna in the non-destructive measurement system has been introduced to reduce the measurement setup space. This project aims to design the Vivaldi antenna by investigating its design dimensions and analyzing the antenna performance by its return loss (S11), Voltage Standing Wave Ratio (VSWR), radiation pattern, and gain. The antenna is designed on the FR-4 substrate with a thickness of 1.5mm (83.9*80.6*1.6mm). Several analyses have been done, which include the Vivaldi design type analysis, the effect of cavity radius, and the feeding type analysis. The proposed Vivaldi antenna has been fabricated using etching techniques and tested using the vector network analyzer. As a result, the proposed design has a resonant frequency of 5GHz and operates in the frequency range of 4.1 to 6 GHz with a return loss below -10dB and VSWR between 1 and 2. The proposed design can send and receive signals with a wide bandwidth, high directivity of 6.8dBi, and a gain of 5.11dBi.